Potato Tuberworm Phthorimaea operculella (Zeller) (Lepidoptera: Gelechioidea) Leaf Infestation Affects Performance of Conspecific Larvae on Harvested Tubers by Inducing Chemical Defenses - Dingli Wang; Qiyun Wang; Xiao Sun; Yulin Gao; Jianqing Ding (Insects, 2020)
Conspecific aboveground and belowground herbivores can interact with each other, mediated by plant secondary chemicals; however, little attention has been paid to the interaction between leaf feeders and tuber-feeders. Here, we evaluated the effect of the foliar feeding of P. operculella larvae on the development of conspecific larvae feeding on harvested tubers by determining the nutrition and defense metabolites in the whole plant (leaf, root and tuber). We found that leaf feeding negatively affected tuber larval performance by increasing the female larval developmental time and reducing the male pupal weight. In addition, aboveground herbivory increased α-chaconine and glycoalkaloids in tubers and α-solanine in leaves, but decreased α-chaconine and glycoalkaloids in leaves. Aboveground herbivory also altered the levels of soluble sugar, soluble protein, starch, carbon (C), nitrogen (N), as well as the C:N ratio in both leaves and tubers. Aboveground P. operculella infestations could affect the performance of conspecific larvae feeding on harvested tubers by inducing glycoalkaloids in the host plant. Our findings indicate that field leaf herbivory should be considered when assessing the quality of potato tubers and their responses to pests during storage.